For a new language of desire: Mary Kelly, Sherrie Levine, Sarah Charlesworth and Barbara Kruger - Bianca Trevisan (piano b, 2016)
During the second half of the 70s artists like Mary Kelly, Sherrie Levine, Sarah Charlesworth and Barbara Kruger, combined by a renewed feminist inspiration and a solid theoretical background, retrieve Freudian and Lacanian theories applying them to the female universe. The condemnation of woman’s subordinate condition does not only unveil the male chauvinism of western society, but also shows the difficulty experienced by the artist in comparing herself with a purely patriarchal code. In all their artworks, be them the creation of a daily archeology (Kelly), the art of appropriation (Levine), the representation of the absence (Charlesworth) or an astute word game (Kruger) - Lacan’s polarity is taken back: under the sign of the presence stands the man, under that of the absence lies the woman, who becomes his fetish, the small object a. Such disparity brings the artists to sadomasochistic mechanisms thus revealing the impossibility to assume an independent dictionary, being unbound from male’s language. To overtake this disparity the artists agree that a “new language of desire” must be established (Laura Mulvey, Visual pleasure and narrative cinema, 1975) to go beyond gender’s roles.